Banking an introductory text - Molyneux, Philip (Macmillan, 1990)
This book provides a detailed coverage of the UK banking and finance system together with an overview of the various theoretical issues relating to banking. The text also analyses the main trends and developments affecting UK and European banks. The implications of 1992 are discussed and the final chapter provides a statistical description and commentary relating to all European Community banking markets.